Topography of the crust-mantle interface under the Western Superior craton from gravity data1 - Nitescu, B; Cruden, A R; Bailey, R C (Canadian journal of earth sciences, 2003)
The Moho undulations beneath the western part of the Archean Superior Province have been investigated with a three-dimensional gravity inversion algorithm for a single interface of constant density contrast. Inversion of the complete gravity data set produces unreal effects in the solution due to the ambiguity in the possible sources of some crustal gravity anomalies. To avoid these effects a censored gravity data set was used instead. The inversion results are consistent with reflection and refraction seismic data from the region and, therefore, provide a basis for the lateral correlation of the Moho topography between parallel seismic lines. The results indicate the existence of a major linear east-west-trending rise of the Moho below the metasedimentary English River subprovince, which is paralleled by crustal roots below the granite-greenstone Uchi and Wabigoon subprovinces. This correlation between the subprovincial structure at the surface and deep Moho undulations suggests that the topography of the crust-mantle boundary is related to the tectonic evolution of the Western Superior belts. Although certain features of the crust-mantle boundary are likely inherited from the accretionary and collisional stages of the Western Superior craton, gravity-driven processes triggered by subsequent magmatism and crustal softening may have played a role in both the preservation of those features, as well as in the development of new ones. [PUBLICATION ABSTRACT]